An assessment of the prescribing skills among second year MBBS students in a tertiary care teaching hospital - Suhaina, Abdul Samath; Supriya, Selvakumar Suseela (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The medical undergraduate curriculum includes training in prescription writing from second year under Pharmacology. This study assesses the prescription writing skills of second year MBBS students in Sree Mookambika institute of medical sciences. The study can promote awareness among the medical students about the rational application of drug prescribing skills. Methods: After ethical clearance from the Institutional research committee, the cross-sectional study was conducted among 115, second year MBBS students who were above 18 years of age. Parameters like patient and doctor information, drug information and legibility of the prescription was assessed. Results: Of the 115 students who participated in the study, only 86 (74.7%) students got a score 4/4 for patient-related information and no student got 5/5 with respect to doctor related information. 98 students (85.2%) got 6/6 with regards to drug information. The most lacking information was the qualification of the doctor, followed by the total quantity of the drug prescribed. The legibility of the prescriptions was also not up to the mark with only 22 students (19.1%) who got a 4/4. Conclusions: The prescription writing skills among second year undergraduate students are suboptimal. Periodic assessment of the students must be done to evaluate their knowledge on prescription writing and the training clinicians must help to fill the knowledge-practice gap. WHO recommended six step prescription writing model must be followed and emphasized among students.